A descriptive comparative study of traditional and nontraditional master's of science in nursing degree programs offering the education track in the state of Florida. - Goetteman MM (Descriptive Comparative Study of Traditional & Nontraditional Master's of Science in Nursing Degree Programs Offering the Education Track in the State of Florida, 2006)
The goal of this research was to determine how the nursing faculty shortage in Florida was being addressed. The purpose of this descriptive, comparative study was to explore program length, size, and admission criteria of master's of science in nursing (MSN) degree programs. Characteristics of both traditional and non-traditional programs that offered the education specialty were examined. Non-traditional programs included registered nurse to master's of science in nursing (RN-MSN) degree programs. Characteristics of students enrolled in the education track of these programs were also compared, based on participant's entry level into nursing practice. The three comparison groups included diploma prepared nurses, associate degree prepared nurses, and baccalaureate prepared nurses. Comparative and descriptive statistics with cross tabulations and frequencies, were used to determine comparisons, based on responses to questionnaire items that focused on reasons for entering the program, financial assistance, program satisfaction, goals, future plans, years of experience, nursing specialty, employment status, and demographics.The literature review found very few current studies on non-traditional and traditional MSN degree programs. Results of this study found only nine programs in the state that offered an MSN with a nursing education specialty with participation elicited from five of those nine programs. Findings revealed that within those programs were a variety of both traditional and non-traditional options that were unique in how they were organized and administered. Descriptive, comparative analysis revealed no significant differences in student characteristics of the three identified groups for those enrolled in master's level coursework in the nursing education specialty in spring of 2006.Overall, participants in the MSN programs indicated that they chose the program because they needed it for advancement, they wanted additional knowledge and skills, and the reputation and location were important. Their education was financed with personal earnings or loans. Upon completion of the program they planned to stay in their current positions and continue for a doctoral degree or specialty certification in nursing. Within 10 years they planned to be working as a faculty member in a nursing program. They were Caucasian women, aged 41--55, who lived with a significant other and children, worked more than 33 hours per week in critical care, pediatrics or education, and had more than 20 years of work experience.Findings indicated that the diversity of the MSN programs made no difference in the types of students that were attracted to the programs. These findings may be used to target recruitment efforts toward those interested in becoming nursing faculty in an effort to help alleviate the nursing faculty shortage in Florida.